Tugas Menyalin Teks Dokkai untuk Meningkatkan Kemampuan Mahasiswa dalam Membaca dan Memahami Teks Berbahasa Jepang - Yudi Suryadi; Diana Puspitasari (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to describe the results of the implementation of the assignment model that is rewriting the dokkai text on the Dokkai course in the Japanese Literature Study Program of FIB UnSoed to improve students' Japanese language skills. This study used the action research method with the assignment of rewriting the dokkai text as its treatment. The research subjects were 107 students of the Japanese Literature Study Program of FIB UnSoed consisting of 4th-semester student class 2017 and 2nd-semester student class of 2018. The data collection used in two ways. They were giving tests and questionnaires to students. The data collected were then analyzed quantitatively and qualitatively to produce a conclusion from this study. Based on the results of data analysis, the results of the test results for the 4th-semester student class 2017 got an average value of 69, the highest score of 96, and the lowest score of 40, while the 2nd-semester student class of 2018 got an average score of 62, the highest score of 94, and the lowest value of 55. Furthermore, from the results of the questionnaire filled out by students, 92.6% of students agreed with the assignment model because of the assignment of rewriting the dokkai text. The students could more fluently read and understand the contents of the text studied in class. At the same time, it trained them to get used to writing Japanese characters, whether it was hiragana, katakana, or kanji.